Multifactor capital asset pricing model in emerging and advanced markets using two error components model - Radamanee Noppasit (2020)
© 2020 Inderscience Enterprises Ltd. We aim to explore the macroeconomic factors that are able to influence the return of the stock market in emerging and advanced markets. To find such factors, we analyse the data from three emerging countries and three developed countries. The multifactor capital asset pricing model (CAPM), which includes the overall market return and the selected macroeconomic variables, is employed to achieve our study. However, the assumption of CAPM, which displayed only one error term, has been concerned in our analysis as one error term may fail to capture and define the whole erroneousness in the model. Thus, we prove the existence of the second error components of the CAPM. In addition, the concept of a seemingly unrelated regression (SUR) model is also applied to join the CAPM of each country. As a consequent, we propose a new SUR model which compounds two errors to investigate the multifactor CAPM.